Crystal structure reveals the hydrophilic R1 group impairs NDM-1–ligand binding via water penetration at L3 - Xiangrui Shi; Huijuan Yang; Yujie Dai; Hui Zhao; Yuhang Li; Yanxi Li; Xin Zhou; Hailong Yan; Qinghua Zhang; Wei Liu (Journal of Structural Biology: X)
The global spread of New Delhi metallo-β-lactamases (NDMs) has exacerbated the antimicrobial resistance crisis. This study resolved the crystal structure of NDM-1 hydrolyzing amoxicillin for the first time, revealed that the hydroxyl group in the R1 moiety of amoxicillin anchors a key water molecule (Wat1) via hydrogen bond, inducing a conformational shift in Met67 (average displacement of 3.8 Å compared to its position in complexes with ampicillin, penicillin G, and penicillin V) and impairing the hydrophobic interaction between the loop 3 and the substrate. Molecular dynamics simulations confirmed that the π-π stacking contact time between amoxicillin and the L3 critical residue Phe70 decreased to 4.3 % (ampicillin: 12.3 %), with a binding energy reduction of 10.5 kcal/mol. Steady-state kinetics showed that amoxicillin exhibited a 2.2-fold higher Km and a 5.2-fold higher kcat compared to ampicillin, demonstrating that hydrophilic R1 groups impair enzyme-substrate binding. This work demonstrates the essential role of hydrophobic interactions in L3-mediated substrate binding and provides a novel strategy for designing L3-targeted NDM-1 inhibitors: maximize hydrophobicity and minimize polar surface area in the L3 contact region to block water penetration, thereby stabilizing the inhibitor-L3 interaction.